Social privilege in the context of therapeutic groups : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts (Psychology), Massey University, Aotearoa New Zealand - Peace, Charlotte E. (Massey University, 2025)
In Aotearoa-New Zealand, mental health services are under strain, and group therapy is increasingly used as a modality that provides economic access to therapy to a large number of people. Therapeutic groups are typically diverse, comprised of a complex constellations of identity dimensions, values, and characteristics. Race, class, gender, sexuality, and religious positions confer privileges, marginalising those not occupying such dominant positions. Privilege can subsequently manifest as tension and conflict between individuals within therapeutic groups. Researchers have noted the need to study how privilege manifests and is managed in therapeutic groups. Furthermore, research tends to focus on oppression and marginalisation in therapy groups as the focal point to address, rather than on privilege as a cause of marginalisation and oppression. Through semi structured interviews, the researcher explores how eight group therapists understand and manage privilege in group therapy. Privilege emerges as relational, dynamic, and complex, presenting partial challenges to social microcosm theory. In therapeutic groups, privilege may not always be held by those who hold it on broader society. Therapists manage the potential risk of privilege having negative effects on group members, either through pre-emptively excluding some privileged people or utilising the exploration of its manifestations as a mechanism for individual change and growth. The findings support the need for targeted training in the understanding and management of privilege in group facilitation.
Keywords: Social Privilege; Privilege; Group Therapy; Therapeutic Groups; Marginalisation; Oppression; Identity Dimensions; Social Construction; Interpretative Phenomenological Analysis; Values; Power Dynamics; Harm; Group Facilitation Approaches; Tension; Conflict; Intersubjective Learning; Social Justice; 441012 Sociology of inequalities; 520303 Counselling psychology